Depressive Symptoms are Frequent in Atypical Parkinsonian Disorders. Issue 2 (24th June 2016) - Almeida, Leonardo; Ahmed, Bilal; Walz, Roger; De Jesus, Sol; Patterson, Addie; Martinez‐Ramirez, Daniel; Vaillancourt, David; Bowers, Dawn; Ward, Herbert; Okun, Michael S.; McFarland, Nikolaus R.
Abstract: Background: The objective of this study was to compare the incidence and prevalence of depressive symptoms in atypical parkinsonian (APD) syndromes versus Parkinson disease (PD). Methods: In a large, retrospective patient cohort, the authors analyzed the incidence and prevalence of depressive symptoms using the Beck Depression Inventory and evaluated patients longitudinally on subsequent visits. For individuals who were followed at subsequent visits, incidence rates were calculated in person‐years as a measure of incidence. Results: In total, 361 patients were identified who had APD syndromes, including progressive supranuclear palsy, corticobasal degeneration, multiple system atrophy, and dementia with Lewy bodies; and 2352 patients with PD were used as a control group. The mean Beck Depression Inventory values were significantly higher in patients with APD (F = 14.19; P < 0.001). A significantly higher proportion of those with APD screened positive for depressive symptoms both at the initial visit and on subsequent visits ( P < 0.001), and depressive symptoms appeared to be more severe in the APD subgroups. Unified Parkinson's Disease Rating Scale motor scores and disease duration were correlated with depressive symptoms. Conclusions: The current results suggest that the incidence and prevalence of depressive symptoms are higher in patients with APD syndromes and also appear to be more severe than those in patients with PD. Depressive symptoms in APD are common and affect patients regardless of disease duration or motor severity.